Kinetic pinning versus capillary pinning of voids at the moving interface during reactive diffusion. (2nd January 2017) - Gusak, Andriy; Zaporozhets, Tetiana; Janczak-Rusch, Jolanta
Abstract: Two mechanisms of the Kirkendall voids pinning at the moving interface are discussed. Besides common Zener pinning, voids can be additionally, kinetically pinned to the interface by the additional vacancy concentration gradient, existing due to unideal vacancy sinks/sources at the interface and at the both sides of it. Kinetic pinning may explain the influence of copper substrate defect prehistory on the pinning behaviour. Capillary pinning is difficult to apply for the cases of voids enveloping by the growing phase.